Release Kinetic Studies of Stevia rebaudiana Extract Capsules from Sodium Alginate and Inulin by Ionotropic Gelation - Juan Pablo Quintal Martínez; Jorge Carlos Ruiz Ruiz; Maira Rubí Segura Campos (Advances in Materials Science and Engineering)
This study was oriented towards encapsulation of S. rebaudiana extract and the study of its release kinetics. The desired encapsulation was achieved by the ionotropic gelation method using sodium alginate and inulin of polymeric constituents. Characterization of the capsules was performed by micrometric properties, encapsulation efficiency, in vitro extract release analysis, and biological activity of released extract. The in vitro release profiles from different capsules were applied on different kinetic models. The prepared capsules were found spherical in shape with diameters ranging from 2.07 to 2.63 mm, having the encapsulation efficiencies of 43.77% and 56.53% for phenolic compounds and steviol glycosides, respectively. The best-fit model with the highest correlation coefficient was observed in the Ritger–Peppas model, indicating diffusion controlled principle. The release exponent n value obtained from the Korsmeyer–Peppas model varied between 0.2273 and 1.1719, confirming that the mechanism of S. rebaudiana extract bioactive compounds release was diffusion controlled.